Los Amigos Orbea y Aguirre Miramón, y la segunda época de la Bascongada - Berriochoa Azcárate, Pedro (Boletín de la Real Sociedad Bascongada de Amigos del País, 2021)
The “Second Vascongada” was a resurrection in San Sebastián of the Society in the context of the Belle Époque. Its beginning (1899-1902) was brilliant, rich and daring in all kind of brilliant initiatives. Then, it came a long decline. The Society contributed to other initiatives that have lasted in the city. In that brilliant beginning, Friends Wenceslao Orbea and Severo Aguirre Miramón were important figures.